The Influence of Teenagers' Perceptions and Knowledge on the Management of "SUCCESS" Waste Banks in Muaro Jambi Regency - Erris; Susi Ariyani; V.A Irmayanti Harahap (Jurnal Multidisiplin Madani, 2022)
The Waste Bank Program is a community-based waste management program which is a waste management concept that integrates the 3R principles of reduce, reuse and recycle with management as close to the source as possible. Reduce is to reduce waste generation at the beginning. Reuse is an attempt to reuse waste or items that are no longer useful, while recycling is recycling waste into other items of economic value. This research is an analytic research, namely research that emphasizes the relationship between one variable and another with a cross sectional research design. The population in this study were all teenagers in Mendalo Laut Village, and the researchers used a total sample of 56 teenagers. The results of the study revealed that there was a significant relationship between the perceptions and knowledge of adolescents regarding the management of the Waste Bank in Mendalo Laut Village, Muaro Jambi Regency in 2022. This can be seen from the statistical test results for each variable that the p-p value is <0.05. After this research, it is hoped that the village leadership will coordinate in an integrated manner with those responsible for managing the Garbage Bank and for the community, especially youth in Mendalo Laut Village, it is hoped that they can provide input so that there is a need to increase public awareness of the importance of waste management, especially through the Garbage Bank program so as to create a safe environment. clean.